Impacts of Traditional Organometallic Interventions on Chronic Uterine Fibroids: A Case Report - Mulla, Sohail; Rathi, Bharat (Asian Journal of Biological and Life Sciences, 2025)
Uterine fibroids are commonly seen benign tumours, leading to reproductive health disorders amongst abnormal bleeding, pelvic discomfort, and infertility. Surgery, including hysterectomy, or myomectomy has conventionally been the primary treatment, with considerable risks and a substantial economic burden. However, non-surgical approaches have been explored throughout history. This study presents a case of a 52-year-old woman with chronic uterine fibroids and associated Symptoms, including abnormal bleeding and severe burning sensations, which were successfully Resolved using traditional organometallic formulations. The patient, after developing symptoms Post-COVID vaccination, sought alternative treatment and was prescribed a combination of Indian classical organometallic formulations, including Rasa Sindoor, Tamra Bhasma, Trivanga Bhasma, and Punarnavasava. Within three months, the patient’s condition significantly improved. Menstrual regularity was restored, bleeding ceased, and the burning sensation subsided. Follow-up imaging showed reduction in fibroid size. Biochemical investigations found within normal ranges, indicating safety and efficacy of the treatment. This case highlights the potential of Ayurvedic and traditional therapies as viable alternatives to surgery in managing uterine fibroids. However, the use of organometallic formulations, while effective, poses safety concerns due to the potential nephrotoxic effects of prolonged heavy metal exposure. Further research is necessary to explore the long-term safety and efficacy of such treatments.
Keywords: Uterine fibroids; Rasashastra; Case report